High temperature pyrolysis behaviour and kinetics of lump coal in COREX melter gasifier. (April 2014) - Zhang, S. F.; Zhu, F.; Bai, C. G.; Wen, L. Y.; Peng, H. J.
Abstract : The COREX process is an industrially and commercially proven smelting reduction process producing hot metal of the same quality as blast furnace ironmaking. The high temperature pyrolysis behaviour of lump coal is crucial important in the COREX melter gasifier, which determines energy utilisation and gas composition, as well as metallurgical property and particle size of semicoke produced. In the present study, an experimental study was carried out to simultaneously investigate the pyrolysis behaviour of two Chinese lump coals used in the COREX process at different temperatures, and the effect of pyrolysis temperature on microstructure of semicoke produced was analysed by X-ray diffraction technology. In addition, the pyrolysis mechanics and the kinetics parameters of two lump coals were obtained. The results show the pyrolysis rate of lump coals is very rapid, the required time to completion of pyrolysis decreases with increasing temperature, and the contents of moisture and volatile have a remarkable effect on the maximum weight loss rate. The pyrolysis process of lump coals includes three stages: the first is water release accompanying a small quantity of devolatilisation, the second is devolatilisation, and the third is stabilisation. It is found the stacking height of graphite-like crystallite layer along the c -axis for the produced semicokes gradually increases with increasing temperature, the micro graphite spacing decreases and the crystallite size increases while raising the pyrolysis activation temperature. Three-dimensional diffusion is the primary restrictive link in the whole pyrolysis process of lump coals, the expression 3/2(1− α ) 2/3 [1−(1− α ) 1/3 ] −1 is the optimal kinetic mechanical function. The apparent activation energy decreases with volatile increasing.